PENGARUH PENGGUNAAN MODEL MAKE A MATCH TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD - Mardiani, Emi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract A problem in this research was â€œhow the influence of the use of a model make a match of the results of the learning of science students social grade V of public elementary school 10 pontianak east ?â€ .This research aims to understand the influence of the use of a model make a match of the results of the learning social science a student of class v sdn 10 pontianak east . Research methodology used his experiments with the form of eksperimen semu (quasi-experiment) with the design eksperimen Nonequivalent Control Group Design.Population in this research is all students grade V A and V B academic year 2016 / 2017 which consisted of 64 people.Sample in this penelian were students grade 5 which consisted of 64 people consisting of 32 the VB ( class control of ) and 32 the V A ( class eksperimen).Instrument gatherer data of student learning the test results obtained from pre test and post test. The results of the study , obtained the average test results final grade control 63,68 and the average test results final grade 74,37 experiments obtained thitung of 3,3445 and ttabel with Î± = 5%percent and dk = 62 as much as , which means thitung (3,3445) > ttabel (1,9993), thus then Ha accepted .Of reckoning as effect size (ES), obtained ice as much as 0,87 ( criteria high ) .This means that learning with the use of the kind of classroom make a match make a difference that high evaluation learning outcomes from the classroom v of public elementary school 10 pontianak east .Â Keyword : Influence, Learning Model Make A Match, Study Result